Early Eocene fossil illuminates the ancestral (diurnal) ecomorphology of owls and documents a mosaic evolution of the strigiform body plan. (22nd August 2022) - Mayr, Gerald; Kitchener, Andrew C.
Abstract : We describe a partial skeleton of a fossil owl (Strigiformes) from the early Eocene London Clay of Walton‐on‐the‐Naze (Essex, UK). The holotype of Ypresiglaux michaeldanielsi, gen. et sp. nov. is one of the most complete specimens of a Palaeogene owl and elucidates the poorly known ecomorphology of stem group Strigiformes. Whereas most of the postcranial bones show the characteristic strigiform morphology, the new species exhibits plesiomorphic features of the skull and cervical vertebrae that differ distinctly from extant owls. A well‐developed supraorbital process of the lacrimal bone suggests that the eyes were not as greatly enlarged and forward‐facing as in extant owls. A plesiomorphic quadrate morphology indicates differences in the otic region, and a proportionally longer axis suggests that the fossil species was not able to rotate its head to the degree found in crown group Strigiformes. Therefore, the fossil documents a mosaic evolution of the strigiform body plan, with owls developing raptorial adaptations before specializations of the visual and acoustic systems evolved. Because the latter relate to a crespuscular or nocturnal activity pattern, we hypothesize that Ypresiglaux was diurnal. Nocturnality in owls may have evolved in response to the emergence of evolutionary opportunities, which enabled owls to exploit new ecological niches, or owls may have been driven into nocturnal habits by ecological competition.